A FEASIBILITY STUDY OF LUNG CANCER DIAGNOSIS BY HIGH INTENSITY PIXELS IN LUNG CT IMAGES - Nigudgi, Surekha; Arabi, Dr Punal M; Patil, Dr G M (The journal of contemporary issues in business and government, 2021)
According to world health organization the most common cancer is the lung cancer considering 1.7 million deaths and two million new cases in 2018.It is the biggest cancer killer in both women and men worldwide. If lung cancer is detected and treated before it metastasizes the chance for a cure would be excellent. The imaging techniques used for detection are chest radiography, computed tomography(CT),MRI and PET. The CAD system is the one which helps the physician for detection of the disease and also gives a second opinion to make the final decision. Here in this study, a method is proposed for computer aided diagnosis (CAD) of lung cancer to study the feasibility of using the number of pixels with high intensity present in the lung CT images . For experimentation total 14 images of cancerous and healthy lungs were taken and the results obtained showed an accuracy of 78%.